EARLY VERSUS LATE ARTERIO-VENOUS FISTULAE: IMPACT ON FAILURE RATE - Farooq, Zahid; Mehmood, Arshad; Saeed, Shahzad; Raja, Khalid Mehmood; Khan, Malik Nadeem Azam; Murtaza, Badar (Journal of Ayub Medical College Abbottabad, 2010)
Background: Haemodialysis is the primary mode of renal replacement therapy for patients of end stage renal disease. The most important determinant for effective haemodialysis is a reliable vascular access. Arterio-venous (AV) fistula is the closest to be an ideal long-term haemodialysis vascular access. The creation of fistulas or grafts is recommended before starting haemodialysis, this study was undertaken to determine the impact of timing of AV fistula creation on its failure rate. Methods: It is a descriptive study. All patients with chronic kidney disease (CKD) reporting to Armed Forces Institute of Urology (AFIU) and Military Hospital (MH) Rawalpindi from January 2008 to October 2009 in whom vascular access was created were included. The patients were followed prospectively and a complete data about their haemodialysis and vascular access was maintained. Results: A total of 168 permanent accesses were created in 112 patients in this study. The mean duration of follow-up was 14.05±4.45 months. Early access creation group included 23 patients and late access creation group included 89 patients. Out of 168 fistulas that were created, 54 fistulas failed with 45 (83.3%) of these from patients of late access creation group. Age, gender and diabetes mellitus (DM) had no significant affect on failure rate of fistulas. Conclusion: Timely referral to nephrologists and early creation of permanent vascular access by dedicated team work can improve the success rate of AV fistulae so enhancing quality of life of patients of end stage renal disease. Keywords: Nephrology consultation, Haemodialysis, Arterio-venous fistula